Makna Berbakti Pada Orang Tua Dalam Perspektif Anak Usia Dini di TK Kasih Maitreya Selatpanjang Kabupaten Kepulauan Meranti - Antina Antina; Irawati Irawati; Rida Jelita (STAB Maitreyawira, 2023)
This study aims to inculcate a devotional attitude in early childhood education at Kasih Maitreya Kindergarten. The research method used was qualitative research in a case study format, the sample was selected by purposive sample, with participants from the head of the education unit and the TK Kasih Maitreya teachers. Data collection by observation, interviews, documentation and triangulation. Data analysis using interactive models (Miles and Huberman, 2014, 247), through data reduction, data presentation, and conclusion/verification. The validity of the data is carried out by validating concepts in the form of triangulation and member checks. From the research it was found that (1) the implementation of devotional learning at Kasih Maitreya Kindergarten starts from religiosity; sociality; democracy; honesty; independence; 5S culture; responsibility and respect for the environment. (2) The implementation of the understanding of devotion towards the development of Kindergarten Kasih Maitreya children has experienced a proud increase, especially in terms of improving early childhood good habits, namely children being able to be polite both to their teachers and to their parents and are able to apply them in everyday life. It is proven by the results of observations of Kindergarten Kindergartners, Kasih Maitreya, which reached 2% Very Good Development (BSB), 76% Developed According to Expectations (BSH) and 22% Started to Develop (MB).